Penggalian Tambang Ilegal yang Terjadi di Kecamatan Sukatani Kabupaten Purwakarta Dihubungkan dengan Peraturan Daerah Kabupaten Purwakarta Nomor 6.A Tahun 2009 Tentang Pengelolaan Pertambangan Umum - Sri Wahyuni; H. Uu Idjudin Solihin (Universitas Batanghari Jambi, 2021)
In mining exploitation in Indonesia, every business actor is required to have a Mining Business License prior to carrying out such mining activities and / or businesses. This permit can be obtained from the government, because a permit is a one-sided government act based on statutory regulations to be applied to concrete events according to certain procedures and conditions. However, in fact there are many mining business actors who carry out mining activities without obtaining a permit, so the author is interested in knowing the factors that cause illegal mining to occur. And the research method used in this writing is using the juridical-normative method, where the data collection techniques are researched through literature studies, law books, and other literature. In addition, the authors also use primary data, namely by conducting interviews with parties who are aware of the illegal mining case. The factor that led to illegal mining excavation in Sukatani Subdistrict, Purwakarta Regency, was the demand for a national project for the Jakarta - Cikampek Toll Road, so this project was used as a justification for mining entrepreneurs to carry out mining activities without having an official permit from the government.